2014
DOI: 10.1177/0300985814560232
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in and Expression of the Tumor Suppressor Gene p53 in Egg-Type Chickens Infected With Subgroup J Avian Leukosis Virus

Abstract: To investigate the molecular mechanisms of the oncogenic effects of avian leukosis virus subgroup J (ALV-J), we examined mutations in and the expression of p53 in the myelocytomas distributed in the liver, spleen, trachea, and bone marrow, as well as in fibrosarcomas in the abdominal cavity and hemangiomas in skin from chickens that were naturally or experimentally infected with ALV-J. Two types of mutations in the p53 gene were detected in myelocytomas of both the experimentally infected and the naturally inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
4
9
0
Order By: Relevance
“…In the infected poultry, the mutation rate of p53 was 60 percent (12/20). Two types of mutations (deletions and point mutations) were detected in the p53, which was consistent with the results reported in previous studies [17]. In the 12 mutated p53 genes, the base sites with high mutation frequency were 651, 786, 828, 864 and 879.…”
Section: Mutations In the P53supporting
confidence: 91%
See 1 more Smart Citation
“…In the infected poultry, the mutation rate of p53 was 60 percent (12/20). Two types of mutations (deletions and point mutations) were detected in the p53, which was consistent with the results reported in previous studies [17]. In the 12 mutated p53 genes, the base sites with high mutation frequency were 651, 786, 828, 864 and 879.…”
Section: Mutations In the P53supporting
confidence: 91%
“…The deleted sequence was located at 631-677 bp in the open reading frame of the reference sequence, resulting in missense mutations from the position 210 to the termination. The short form of p53 transcript was also found at the cases infected avian leukosis virus [17]. A series of missense mutations from the position 163 to the termination due to a base deletion were found in an experimentally infected chicken.…”
Section: Discussionmentioning
confidence: 89%
“…In the infected poultry, the mutation rate of p53 was 60 percent (12/20). Two types of mutations, deletions and point mutations (single-point mutations and multiple-point mutations), were detected in the p53, which was consistent with the results reported in previous studies [22]. In the 12 mutated p53 genes, the base sites with high mutation frequency were 651, 786, 828, 864 and 879.…”
Section: Mutations In the P53supporting
confidence: 91%
“…These mutations are mainly point mutations, which are frequently inactivated by base deletions and insertions; majority of p53 mutations are missense mutations [27]. In the current study, found after Qu's research [22]. In the present research, it is found that the p53 has high mutation frequency of 60% in poultry oncology, and the mutation region is mainly concentrated in the DBD.…”
Section: Discussionsupporting
confidence: 53%
“…Similar to various other cancers, the occurrence of glioma is associated with genetic mutations in p53 (20)(21)(22)(23)(24). The alteration or inactivation of p53 induced by mutations or its interaction with oncogene products of DNA tumor viruses may lead to cancer (25). Low p53 expression occurs in glioma, which leads to dysfunction of the p53-associated regulatory pathways (26).…”
Section: Overexpression Of P53 Delivered Using Recombinant Ndv Inducementioning
confidence: 99%